Supercontinuum Micrometer-Displacement Sensor Using Single-Multi-Air-Gap-Single Mode Fiber as Sensing Probe - Ahmad, Harith; Aidit, Siti Nabila; Ooi, Shok Ing; Tiu, Zian Cheak (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In this paper, a displacement sensor utilizing a Mach-Zehnder interferometer with a single-multi-air-gap-single mode (SMAS) fiber structure is proposed and demonstrated. A 30-cm-long four-mode step index fiber (FMSIF) is used as the multimode fiber in the SMAS structure, with the left end of the FMSIF fusion spliced to a 50-cm-long single-mode fiber (SMF-28). The right end of the FMSIF is aligned to another 50-cm SMF-28 on the v-groove of Fitel S178A fusion splicer but without splicing, creating an air gap with a tunable length of 0-300μm. The performance of the displacement sensor is investigated over the range of 1.1-1.7μm using a supercontinuum source. Through the experiment wavelength range, the highest sensor sensitivity is achieved at 1.7 μm with a sensitivity of 12.3 pm/ μm and an R2 coefficient of 0.926. The implementation of a displacement sensor utilizing the simple and cost-effective concept of the SMAS will be beneficial for use in various areas, such as biomedicine, manufacturing, and engineering.